Management of herbicide-resistant Phalaris minor in wheat by integration of malathion and post-emergence herbicides - Anmol; Navish Kumar Kamboj; V. S. Hooda; Meenakshi Sangwan; Aman Karwasra (Annals of Agricultural Research, 2022)
A field study was conducted during Rabi 2019-20 at Agronomy Research Farm of CCS Haryana Agricultural University, Hisar. The experiment comprised of seven post emergence herbicides (clodinafop 9% + metribuzin 20% (RM) (ACM-9), clodinafop 12% + metribuzin 42% (RM) (Shagun), metribuzin, isoproturon, sulfosulfuron, meso+iodosulfuron and pinoxaden) and their integration with malathion at different doses along with weed free and weedy check treatment. Among the treatments where herbicides were applied without integration with malathion, significantly taller plants, more dry matter accumulation, higher number of tillers and LAI were observed under pinoxaden, which remained significantly higher than all other herbicides, whereas, the values of these parameters considerably reduced after the integration with malathion as compared to solitary application of herbicides, except malathion fb pinoxaden. Weed free plots followed by pinoxaden at 50 g/ha and malathion fb pinoxaden at 1000 fb 50 g/ha resulted in higher number of tillers and more dry matter accumulation. Weed free plots recorded higher yield attributes i.e. effective tillers (408 tillers/m2 ) and higher grain yield (5764 kg/ha) followed by application of pinoxaden at 50g/ha. The maximum weed control efficiency at harvest was recorded under weed free situations and was at par with malathion fb meso+iodosulfuron at 1000 fb 14.4 g/ha and malathion fb Shagun at 1000 fb 270 g/ha whereas, minimum WCE was recorded with isoproturon at 1000 g/ha (34.29 %). Integrated application of herbicides and malathion recorded lower weed density, dry weight of Phalaris minor and higher weed control efficiency as compared to solitary application of herbicides.